THE LANGUAGE OF RESEARCH: ARGUMENT METAPHORS IN ENGLISH AND LITHUANIAN - Šeškauskienė, Inesa (Vertimo studijos, 2017)
The paper sets out to examine the lemma argument* in English and Lithuanian academic discourse. Supporting the claim that academic discourse is largely metaphorical, the present investigation is driven by the conceptual theory of metaphor and aims to uncover the metaphors manifested in the contexts of argument/s and argumentation. The data has been collected from the academic section of the British National Corpus (BNC) and the Corpus of Academic Lithuanian (CoraLit). The results have demonstrated that English and Lithuanian share a number of metaphors, such as research / argument is an object, research / argument is a building / structure, research / argument is a person, research / argument is verbal communication and some others. However, the image rendered by the argument in both languages seems to be different—English gives preference to the ‘embodied’ argument, whereas Lithuanian is more confined to treating it as an object. The research has also uncovered interesting language-specific realisation of all metaphors.